Pendalaman Materi Dan Teknik Cepat Penyelesaian Ujian Akhir Pada Guru-Guru Ekonomi SMA/SMK Se-Lombok Barat - Nikensari, Sri Indah; Sri Rahayu, Endang (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
This community service activity (Penmas) aims to improve the understanding of the materials and techniques of completing the final exam with a double syllabus, namely the Curriculum syllabum 2013 and the spirit of the 2006 Curriculum, at high school level Economics teachers in Mataram - Lombok.Penmas conducted for 3 hours, with lecture and practice methods. Selection of materials based on previous years test questions that are often tested and required calculation or curve analysis, such as demand and supply concepts, price elasticity, and transaction analysis in accounting records. The concept of demand and supply material is deepened by the factors that influence it and its impact on the movement / shift of the curve. The concept of elasticity material deepened with the variation of the problem and how to quickly solve it. The transaction analysis material to post in the ledger deepened with some practice with various kinds of questions. The techniques of performing the final exam with multiple choice questions, both manual and computer-based systems are also delivered.Penmas implementation ends with frequently asked questions and submission of several frequently tested material files. This activity will be followed up later, in order to see the effect of this activity on student exam results in the coming year.